PENGGUNAAN METODE INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN GILI BARAT: THE USE OF INQUIRY METHOD TO IMPROVE MATHEMATICS LEARNING OUTCOMES OF GRADE IV STUDENTS OF WEST GILI SDN - Saroro, Efifani Krimitha; Setyawan, Agung (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
This study is to determine and examine “Efforts to Improve Mathematics Learning Using the Inquiry Method at SDN Gili Barat”. This research was conducted using several constructivistic math learning strategies. This type of research is qualitative research that looks and listens more closely and in detail to individual explanations and understandings of their experiences. The constructivistic strategy and inquiry method are based on the researcher's interest in examining more deeply the phenomena experienced by key informants. The research was conducted at SDN Gili Barat Kamal. The informants in this study were teachers, principals, students. Data collection was carried out using several techniques, namely; (a) observation; (b) interviews; and (c) documentation studies. To ensure the validity of the data, several efforts were made as follows: (a) extending the data collection period, (b) making continuous and serious observations, (c) triangulating, and (d) involving peers to discuss. From the results of the review in this study, it was found that there were efforts to improve mathematics learning, which produced students who had noble character, independence, critical reasoning, creativity, mutual cooperation, and a sense of diversity. The principal encourages a variety of participatory, unique, and innovative programs to improve mathematics learning. Fostering cooperation with teachers who support math learning.